Spiritual intelligence and emotional intelligence on employee performance: analysis of organizational citizenship behavior as a mediating variable - Tehubijuluw Zacharias (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
The importance of OCB as behavior outside of the responsibility greatly affects the effectiveness of the organization, namely helping to increase the productivity of colleagues, managerial productivity, efficiency of organizational resources, reducing the level of need for the provision of organizational resources, can increase the stability of organizational performance and increase the ability organizations to adapt more effectively to changes in their environment. This study aims to analyze the mediating effect of OCB in influencing spiritual intelligence and emotional intelligence on employee performance. This study uses an explanatory research approach with data collection carried out simultaneously in one stage or cross-sectionally through a questionnaire.The population used in this study were all employees of the Regional Inspectorate of Maluku Province as many as 85 people. The method of determining sample is full sampling. Data were analyzed by path analysis that modified form of regression analysis in which the independent variables studied not only directly affect the dependent variable, but it can also affect these variables indirectly. The results showed that : spiritual intelligence has a direct effect on employee OCB, emotional intelligence has a direct effect on employee OCB, OCB has a direct effect on employee performance, spiritual intelligence has a direct effect on employee performance, emotional intelligence has a direct effect on employee performance and OCB mediates the influence of spiritual intelligence and emotional intelligence on performance.